Sosialisasi dan Edukasi UU ITE Siswa SMK Muhammadiyah 3 Tangerang Selatan, Etika Komunikasi Media Sosial - Siti Holisah; Luthfy Rijalul Fikri (BADAN PENERBIT STIEPARI PRESS, 2025)
Social media has become a dominant public space used by teenagers for expression, networking, and virtual interaction. In Indonesia, Vocational High School (SMK) students are one of the active social media user groups with high creative potential, but are also vulnerable to misuse due to low digital literacy. Frequent phenomena include the use of harsh language or hate speech, the spread of unverified information (hoaxes), and violations of digital privacy that can impact reputation and legal aspects. This study aims to analyze the understanding and application of communication ethics on social media among students of SMK Muhammadiyah 3, South Tangerang City, while identifying the gap between their theoretical understanding and actual practice. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews and observations during the socialization of the Electronic Information and Transactions Law (UU ITE). The theoretical framework used is Communication Ethics according to Johannesen (2002), which emphasizes the principles of responsibility, honesty, and respect for the rights of others in public communication. The results show that most students understand the basic concepts of legal norms and communication ethics, but their implementation in social media activities is still limited. Contributing factors include a lack of awareness of legal consequences, the influence of peer groups, and a lack of critical thinking skills before sharing content. These findings highlight a significant gap between digital knowledge and behavior. In conclusion, a sustainable and contextual digital literacy education program is needed, emphasizing not only legal aspects but also building ethical awareness, reflective skills, and the ability to manage digital identities responsibly. This will enable students to become intelligent, critical, and ethical social media users.